2016
DOI: 10.1038/hgv.2016.18
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations in the COL2A1 gene in Japanese patients with Stickler syndrome

Abstract: Stickler syndrome is an inherited connective tissue disorder that affects the eyes, cartilage and articular tissues. The phenotypes of Stickler syndrome include congenital high myopia, retinal detachment, premature joint degeneration, hearing impairment and craniofacial anomalies, such as cleft palate and midline facial hypoplasia. The disease is genetically heterogeneous, and the majority of the cases are caused by mutations in the COL2A1 gene. We examined 40 Japanese patients with Stickler syndrome from 23 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Richards et al focused on the exon 2 and found that the phenotypes, which resulted from COL2A1 variants in exon 2, are characterized by predominantly ocular disorders (eg, retinal detachment) . STL 1 has a higher incidence than other type II collagenopathies, and large cohorts of patients have been previously examined by researchers in numerous countries . Wagner disease (MIM #143200) is a rare vitreoretinal degeneration, which is usually caused by mutation of VCAN .…”
Section: Resultsmentioning
confidence: 94%
“…Richards et al focused on the exon 2 and found that the phenotypes, which resulted from COL2A1 variants in exon 2, are characterized by predominantly ocular disorders (eg, retinal detachment) . STL 1 has a higher incidence than other type II collagenopathies, and large cohorts of patients have been previously examined by researchers in numerous countries . Wagner disease (MIM #143200) is a rare vitreoretinal degeneration, which is usually caused by mutation of VCAN .…”
Section: Resultsmentioning
confidence: 94%
“…The clinical findings and mutations in the COL2A1 gene of 21 of the patients have been reported in detail. 2 , 15 17 The remaining five patients were newly studied, and the associated mutations in the COL2A1 gene were c.3624del (predicted to p.Gly1209Valfs*18, NM_001844.4) for Patient 1, c.3188_3211delinsGT (p.Ala1063Glyfs*60) for Patient 6, c.2353C>T (p.Arg785*) for Patient 7, and c.1957C>T (p.Arg653*) for Patient 2. Patient 25 was a family member of Patient 24.…”
Section: Methodsmentioning
confidence: 99%
“…About 80% to 90% of the cases are caused by mutations in the COL2A1 gene. 2 4 The ocular features of Stickler syndrome are characterized by high myopia, retinal detachments, vitreous degeneration, and presenile cataracts. 1 – 4 …”
mentioning
confidence: 99%
“…Although the affected patients in the present study had different genetic mutations, they exhibited similar clinical presentations of retinal detachment and degeneration. Previous studies have also reported that different mutations in COL2A1 can lead to similar phenotypes, with various degrees of expressivity ( 42 , 49 ). The majority of COL2A1 mutations identified in Stickler syndrome are loss-of-function mutations, as they are predicted to result in nonsense-mediated decay of transcripts ( 42 ).…”
Section: Discussionmentioning
confidence: 86%